2008
DOI: 10.1007/s00213-008-1172-1
|View full text |Cite
|
Sign up to set email alerts
|

The antipsychotic potential of l-stepholidine—a naturally occurring dopamine receptor D1 agonist and D2 antagonist

Abstract: Thus, l-stepholidine shows efficacy like an "atypical" antipsychotic in traditional animal models predictive of antipsychotic activity and shows in vitro and in vivo D(1) agonism, and, if its rapid elimination does not limit its actions, it could provide a unique therapeutic approach to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
1
34
2
Order By: Relevance
“…Thus, we can argue that the suppression of locomotion by antipsychotics is specific to hyperactivity induced by MK-801 and is not a consequence of motor impairment due to ataxia/sedation. Although a comprehensive evaluation of antipsychotics in a single model has been lacking, the most commonly prescribed compounds (haloperidol, clozapine, olanzapine, risperidone, ziprasidone and aripiprazole) have been well characterised in several rodent models of positive symptoms of schizophrenia, including those that are based on locomotor hyperactivity induced by the NMDA receptor antagonists in rats and in mice (Castellani and Adams 1981;Kitaichi et al 1994;Maurel-Remy 1995;Ninan and Kulkarni 1999;Nilsson et al 1997;Natesan et al 2008;Leite et al 2008;Nordquist et al 2008). It should be noted, that unlike the present findings, effects of antipsychotics on locomotor hyperactivity from earlier reports are often confounded by non-specific reduction of spontaneous locomotor activity Andiné et al 1999;Zocci et al 2005;Nordquist et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can argue that the suppression of locomotion by antipsychotics is specific to hyperactivity induced by MK-801 and is not a consequence of motor impairment due to ataxia/sedation. Although a comprehensive evaluation of antipsychotics in a single model has been lacking, the most commonly prescribed compounds (haloperidol, clozapine, olanzapine, risperidone, ziprasidone and aripiprazole) have been well characterised in several rodent models of positive symptoms of schizophrenia, including those that are based on locomotor hyperactivity induced by the NMDA receptor antagonists in rats and in mice (Castellani and Adams 1981;Kitaichi et al 1994;Maurel-Remy 1995;Ninan and Kulkarni 1999;Nilsson et al 1997;Natesan et al 2008;Leite et al 2008;Nordquist et al 2008). It should be noted, that unlike the present findings, effects of antipsychotics on locomotor hyperactivity from earlier reports are often confounded by non-specific reduction of spontaneous locomotor activity Andiné et al 1999;Zocci et al 2005;Nordquist et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds with mixed D1 agonist/D2 antagonist profiles have also been suggested as potential antipsychotics effective in treating a broader range of symptoms of schizophrenia (Natesan et al 2008), including negative symptoms (e.g. anhedonia, asociality, blunted affect) and/or cognitive disruptions, which are not well treated by current antipsychotic medications (Young et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…L-stepholidine, one such compound, has been the focus of interest as a putative antipsychotic because of its combined DA D2 antagonist/DAD1 agonist properties [124]. Interestingly, it was recently reported that l-stepholidine (0.1, 0.3 or 1 mg/kg) produced selective suppression of CAR in rats with a favorable EPS liability profile, as well as showing effects in an animal model of negative symptoms [125]. Striatal D2 and D1 receptor occupancy following l-stepholidine 1 mg/kg (estimated from D2 occupancy graphics by l-stepholidine in [125]) seems to be around 45-50 % and 12 %, respectively, and the ED50 dose in the CAR test was reported to be 0.27 mg/kg.…”
Section: Da D2 Antagonist/dad1 Agonist -L-stepholidinementioning
confidence: 99%